The Moderating Role of Institutional Quality on the Nexus Between NPL and Performance Metrics of ROE, ROA and CAR - Abraham Okine (Rev); David Kwashie Garr (Yayasan Ilomata, 2025)
The study explores the moderating effect of institutional quality (INSTQ) on the nexus amongst NPLs and bank performance in Ghana. Employing fixed-effects panel data from 2007 to 2021, and controlling for unobserved heterogeneity, the study offered robust insights into credit risk forces in a developing economy. The discoveries disclose a contradictory positive, and substantial relationship between NPLs and ROA and CAR. However, the influence of NPLs on ROE was positive, but not statistically substantial. Institutional quality exerted direct and significant influence on ROA, ROE and CAR. The interface term operating between NPLs and institutional quality is negative, demonstrating that INSTQ effectively decreases the influence of NPL on performance. Thus, the effects of NPLs on performance are significantly reduced in environments with stronger institutional qualities. While inflation rate shows negative and insignificant relationship with performance, GDP growth is positively related to ROE, albeit insignificant for ROA and CAR. The originality of this study lies in its empirical demonstration of the controlling role of INSTQ in an emerging economy. These findings have significant policy implications, underscoring the need to strengthen regulatory institutions and credit risk governance. Future research needs deeper investigation into the specific disaggregated dimensions of institutional quality and the impacts on performance.